STRATEGI KEPALA MADRASAH DALAM MEWUJUDKAN MADRASAH PLUS KETERAMPILAN - Wahyudi, Kacung; Nurma Yunita; Abdul Aziz (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2023)
Madrasah plus keterampilan is a series of methods used to achieve the goals set by the madrasah head to produce graduates who are not only competent in academic fields but also skilled in practical areas and capable of competing in the business world or job market. The purpose of this research is to analyze the strategies of the madrasah head in realizing a madrasah plus keterampilan (madrasah plus skills) through collaboration with external stakeholders at Madrasah Aliyah Negeri 2 Pamekasan, as well as the supporting and hindering factors in achieving a madrasah with the addition of skills through collaboration with external stakeholders. This study adopts a qualitative approach with a descriptive type. Data sources were obtained through semi-structured interviews, non-participant observations, and documentation. The results of this study indicate that 1) the strategies used by the madrasah head include identifying the real needs of the community, conducting socialization, and collaborating with external stakeholders. 2) Supporting factors include existing programs, good student enthusiasm, adequate facilities, competent teachers, and coordination (collaboration) between teachers and the deputy head of the madrasah. Hindering factors include uncomfortable practice spaces and less effective implementation timing for learning activities.